2012
DOI: 10.1111/j.1467-954x.2011.02048.x
|View full text |Cite
|
Sign up to set email alerts
|

Difficult Friendships and Ontological Insecurity

Abstract: In this paper we explore some of the negative aspects of friendship. In so doing we do not seek to join the debate about whether or not friendships are more or less important than other relationships but rather to explore precisely how significant friendships can be. Based on written accounts submitted to the British Mass Observation Project, we analyse how friendship, when it goes wrong, can challenge one's sense of self and even produce ontological insecurity. Friendship, it is argued, is tied into the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 19 publications
(22 reference statements)
2
66
0
1
Order By: Relevance
“…Perhaps the best known of this literature theorizes contemporary spousal or marriage relationships as 'pure relationships' (Giddens, 1996) or 'liquid love' (Bauman, 2003). Ray Pahl (2000) and other sociologists of friendship (Allan and Adams, 2007;Badhwar, 2008;Rawlins, 1992;Smart et al, 2012) argue that friendship relationships are also patterned by social and historical contexts. Contemporary friendship, they argue, is a chosen relationship, albeit usually forged with people of our own gender and social status.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the best known of this literature theorizes contemporary spousal or marriage relationships as 'pure relationships' (Giddens, 1996) or 'liquid love' (Bauman, 2003). Ray Pahl (2000) and other sociologists of friendship (Allan and Adams, 2007;Badhwar, 2008;Rawlins, 1992;Smart et al, 2012) argue that friendship relationships are also patterned by social and historical contexts. Contemporary friendship, they argue, is a chosen relationship, albeit usually forged with people of our own gender and social status.…”
Section: Introductionmentioning
confidence: 99%
“…Friends may well assume a central role in reassuring the modern individual regarding the continuity of their self-identity, reaffirming a "sense of the reliability of persons and things, so central to the notion of trust" ( [33], p. 92). Confirming this, and inverting the perspective, Smart et al [11] have shown how difficult friendships install in the individual a feeling of existential anxiety and ontological insecurity, because they seriously, and sometimes permanently, jeopardize interpersonal trust (this state of existential anxiety and fear being the precise opposite of trust [33]). …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, within the overall study, spouses with dementia -particularly wives -evinced a degree of vulnerability about their increasingly dependent status within their marital relationships (Boyle, 2013). Similarly, Smart et al (2012) suggest that women are more likely than men to be open about their perceived vulnerability within relationships. Whereas dementia research often focuses on self-esteem as an internally derived form of self-conception, which becomes susceptible to the invasive effects of the illness (eg, Brod et al, 1999), of course social relations influence our social esteem (Honneth, 1995).…”
Section: Using Emotion As a Moral Guide To Social Lifementioning
confidence: 99%
“…Accordingly, some people with dementia in the study conveyed a sense of 'ontological insecurity' -for example via their anxiety -particularly when they had limited ability to probe others about their actions (Smart et al, 2012). Indeed, within the overall study, spouses with dementia -particularly wives -evinced a degree of vulnerability about their increasingly dependent status within their marital relationships (Boyle, 2013).…”
Section: Using Emotion As a Moral Guide To Social Lifementioning
confidence: 99%
See 1 more Smart Citation